1998
DOI: 10.1073/pnas.95.11.6504
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of γ-aminobutyric acid and glycine receptors change alcohol cutoff: Evidence for an alcohol receptor?

Abstract: Alcohols in the homologous series of nalcohols increase in central nervous system depressant potency with increasing chain length until a ''cutoff'' is reached, after which further increases in molecular size no longer increase alcohol potency. A similar phenomenon has been observed in the regulation of ligand-gated ion channels by alcohols. Different ligand-gated ion channels exhibit radically different cutoff points, suggesting the existence of discrete alcohol binding pockets of variable size on these membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
199
3
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(219 citation statements)
references
References 27 publications
14
199
3
1
Order By: Relevance
“…Other investigators have presented evidence that alcohols and anesthetics are able to bind to a site formed by residues in the M2 and M3 domains of GABA A and glycine receptors and regulate channel function in a manner that is dependent upon volume occupation of the site (18,20,30,31). In this study, we did not initially observe a relation between ethanol sensitivity and molecular volume of the substitution at NR2A(Met 823 ).…”
Section: Discussioncontrasting
confidence: 39%
“…Other investigators have presented evidence that alcohols and anesthetics are able to bind to a site formed by residues in the M2 and M3 domains of GABA A and glycine receptors and regulate channel function in a manner that is dependent upon volume occupation of the site (18,20,30,31). In this study, we did not initially observe a relation between ethanol sensitivity and molecular volume of the substitution at NR2A(Met 823 ).…”
Section: Discussioncontrasting
confidence: 39%
“…Molecular modeling studies of alcohol-binding sites in the GABA A and glycine receptors have identified a potential site as a hydrophobic pocket formed by amino acids from the second and third transmembrane domains 6,9,[35][36][37] . The recent structure of the transmembrane domains of the Torpedo n-acetylcholine receptor (nAchR) supports this model 38 and suggests the alcohol-binding site is in a pocket between the transmembrane helices.…”
Section: Towards a "High-affinity" Alcohol Binding Sitementioning
confidence: 99%
“…4 and 5). Single point mutations in these sites can abolish or dramatically reduce the sensitivity to ethanol [6][7][8] or can change the length of the alcohol that affects receptor function 9 . It is proposed that alcohols stabilize a conformation of the receptor with altered function that persists until the alcohol is removed (reviewed in refs.…”
Section: Introductionmentioning
confidence: 99%
“…Position 15′ of the 5-HT 3A receptors TM2 domain is a non-pore-facing amino acid residue (Reeves et al, 2001;Panicker et al, 2002). In addition to its role in channel gating, the amino acid residue at 15′ also appears to have important roles in channel modulation by alcohol and anesthetics (Mihic et al, 1997;Wick et al, 1998), and binding of these drugs to a hydrophobic pocket involving this residue alters receptor function. In a separate study, we have demonstrated that L293 is critical for alcohol actions on the 5-HT 3A receptor; and L293C and L293S mutations abolish alcohol modulation (Hu et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…2A. Residue L293 is in the same 15′ position as a residue in the GABA A receptor that has important roles in channel gating (Findlay et al, 2001;Scheller & Forman, 2002) and modulation by alcohols and general anesthetics (Mihic et al, 1997;Wick et al, 1998). This amino acid residue is thought to reside on the non-porefacing side of TM2 domain (Panicker et al, 2002;Reeves et al, 2001).…”
Section: Role Of L293 In the Modulatory Action Of 5-himentioning
confidence: 99%